THE EFFECT OF DISCIPLINE AND QUALITY OF HUMAN RESOURCES ON PERFORMANCE MEDIATED BY LOYALTY VARIABLES - Andreas Kurniawan Santoso; Rudi C Tarumingkeng; Eka Desy Purnama (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2022)
The purpose of the study was to determine the effect of discipline and the quality of human resources on performance mediated by the loyalty of credit marketing officer at PT. Maybank Indonesia Finance. The research population in this study amounted to 804 people with the sample used 73 respondents. This research will be conducted in the period between January 2021 to March 2022. The type of research used is the Explanatory Survey method, with the Non-Probability Sampling technique. Data collection techniques used are questionnaires and observations, as well as literature study. The data analysis technique uses the smartPLS-SEM (Partial Least Square–Structural Equation Modeling) tool. The results of the study showed that there was a significant effect of discipline on performance with a T-statistic value of 2.233. There is a significant influence of the quality of human resources on performance with a T-statistic value of 2.051. There is a significant effect of discipline on employee loyalty with a T-statistic value of 2,934. There is a significant influence of the quality of human resources on employee loyalty with a T-statistic value of 4.949. There is no significant effect of employee loyalty on performance with a T-statistic value of 1.335. There is no significant effect of employee loyalty in mediating discipline on performance with a T-statistic value of 1.224. There is no significant influence of loyalty in mediating the quality of human resources on performance with a T-statistic value of 1.303.